Preparation of Functional Food with Enhanced Antioxidant Properties by Adding Aronia melanocarpa Polyphenol Honey - Jingyi Wang; Jiahui Hao; Jie Wang; Siyu Wang; Ziluan Fan (Foods, 2024)
To enhance the functionality of honey, particularly its antioxidant capacity, the incorporation of Aronia melanocarpa polyphenols (AMPs) is an effective approach. The preparation technology and antioxidant activity of AMP added to honey were studied. AMP was extracted with ethanol and its components were analyzed and then mixed evenly with honey in different addition amounts (0.1~0.5% w/w). The product was characterized based on the active ingredients (total phenols, total flavonoids, and anthocyanin content) and antioxidant activity (DPPH, ABTS, and reducing power) during storage to obtain the optimal storage time. The optimal polyphenol addition amount was determined by combining honey enzyme activity (amylase, glucose oxidase, and sucrase), sensory evaluation, and acute cell toxicity experiments. The optimal preparation process is an addition of 0.4% AMP and a storage time of 14 days or more. The active ingredients of the product are positively correlated with the AMP addition, and the antioxidant activity is significantly improved (from two to eight times). AMP exhibits a notable inhibitory effect on enzyme activity, with concentrations ranging from 0.1% to 0.4%, resulting in enzyme activity levels in honey remaining at 75% or higher. Honey samples containing 0.1% to 0.5% AMP exhibit minimal to no acute toxicity to cells. AMP can improve the nutritional value of honey, imparting unique color and flavor while enhancing its antioxidant activity. As such, it holds significant potential as a novel functional food.